Method for activating oxidation reduction of layered oxide oxygen ions by ZrO2 coating

By coating layered oxides by ZrO2, the problem of oxygen ion dissolution is solved, and the cycle stability and electrochemical performance of the positive electrode material of sodium ion battery are improved.

CN119650670AInactive Publication Date: 2025-03-18GUIZHOU MEILING POWER SUPPLY CO LTD

Patent Information

Application Number
CN202510093392.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While activating the redox reaction of layered oxide oxygen ions, controlling the dissolution of oxygen ions is a problem that has yet to be solved, affecting the cyclic stability of the material.

Method used

The method of activate layered oxides by ZrO2 coating is adopted, and the mixture is uniformly mixed by ball milling and sintering is carried out to form a uniform ZrO2 coating layer, which hinders the reaction of electrolyte with the material and controls the dissolution of oxygen ions.

Benefits of technology

It effectively improves the cyclic stability and discharge specific capacity of the material, inhibits the dissolution of oxygen ions, and improves the stability and electrochemical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650670A_ABST
    Figure CN119650670A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of a sodium ion battery positive electrode material, in particular to a method for activating oxidation reduction of layered oxide oxygen ions by adopting ZrO2 coating and adopts a resonance mode of gradient rotation and revolution (gradient rotation resonance) to enable a very small amount of ZrO2 to be uniformly dispersed in layered oxide particles. Therefore, ZrO2 is uniformly coated on the surface of the layered oxide; the synergistic effect of ZrO2 coating and Zr < 4 + > doping can catalyze the oxidation-reduction reaction of oxygen ions of the layered oxide within the voltage range of 2-4 V, the dissolution of the oxygen ions is inhibited while the extra discharge gram specific capacity is provided, and the interface stability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of positive electrode materials for sodium ion batteries, and in particular to a method for activating the redox of oxygen ions in layered oxides by coating with ZrO2. Background Art

[0002] Sodium-ion batteries are considered to be a promising alternative to lithium-ion batteries because of their good high and low temperature performance, environmental friendliness, and similar intercalation compound structure and similar charge and discharge mechanism to lithium-ion batteries. However, the lower energy density and shorter cycle life of sodium ions have severely limited the development of sodium-ion batteries.

[0003] At present, some effective measures have been taken to improve the energy density and cycle stability of layered oxides. For example, CN202410603642.4 discloses a binary sodium ion battery positive electrode material and its preparation method and application. This method prepares a binary precursor with excellent morphology by alloy electrolysis, so that the synthesized layered oxide has more excellent morphology and electrochemical properties. In addition, this method reduces the voltage window from 1.5 to 4.3 V to 1.5 to 4 V, inhibits the irreversible phase change of the material in the high voltage range, and thus improves the material cycle stability; such as CN202410610216.3 Disclosed is a preparation method for reducing the solid-phase sintering temperature of layered oxides for sodium ion batteries. The method prepares layered oxides for sodium ion batteries by a granulation and sintering method, which significantly reduces the sintering temperature of the material and makes the sintering uniformity more excellent, thereby obtaining excellent electrochemical performance. For example, CN202411664481.6 discloses a method for simply activating the redox of oxygen ions in sodium ferromanganate positive electrode materials. The method uses nitric acid to provide a strong oxidizing environment to control the Mn valence state inside the material, thereby causing the oxygen ions in the material to undergo a redox reaction, thereby providing the material with additional discharge gram-specific capacity. In summary, the materials synthesized by the above three methods all have excellent performance, but the first two methods do not significantly improve the energy density of the material, and although the latter method activates the redox reaction of oxygen ions to provide capacity, the dissolution of oxygen ions seriously affects the cycle stability of the material, causing its cycle performance to be seriously reduced.

[0004] Therefore, controlling the dissolution of oxygen ions while activating the redox reaction of layered oxide oxygen ions is a problem that needs to be solved. Summary of the invention

[0005] In order to solve the above-mentioned technical problems existing in the prior art, the present application provides a method for activating the redox of oxygen ions in layered oxides by coating with ZrO2, which is specifically achieved through the following technical scheme.

[0006] A method for activating the oxygen ion redox of layered oxides by ZrO2 coating, and the chemical formula of the layered oxide is Na x TMO2, where 0.44 < x < 0.8, and TM is selected from one or more of Fe, Mn, Ni, Al, Cu, and Zn. The method specifically includes the following steps:

[0007] (1) Weigh the sodium source and the transition metal source TM according to the molar ratio of each element in the chemical formula and place them in a ball milling jar. After ball milling and mixing evenly, a mixed powder is obtained;

[0008] (2) Transfer the mixed powder in step (1) to a porcelain boat, place the porcelain boat in a tube furnace, sinter at a high temperature in an air atmosphere, then cool down to room temperature and take out the sintered product. Grind the sintered product into powder and sieve it to obtain the layered oxide of sodium ion battery Na x TMO2;

[0009] (3) Place the layered oxide obtained in step (2) in a ball milling jar, weigh 1 - 3 wt% of ZrO2 based on the mass of the layered oxide and place it in the ball milling jar. Then put the ball milling jar into a planetary ball mill and perform ball milling in a double ball milling mode; finally, a uniformly ball milled mixed powder is obtained;

[0010] (4) Transfer the mixed powder in step (3) to a porcelain boat, place the porcelain boat in a tube furnace, sinter at a high temperature in an air atmosphere, then cool down to room temperature and take out the sintered product. Grind the sintered product into powder and sieve it to obtain the ZrO2 - coated layered oxide of sodium ion battery n%ZrO2@Na x TMO2, where 1 < n < 3, 0.44 < x < 0.8, and TM is selected from one or more of Fe, Mn, Ni, Al, Cu, and Zn.

[0011] Further, the sodium source in step (1) is one of NaOH, Na2CO3, NaHCO3, NaCl, and CH3COONa. To compensate for the loss of the sodium source during high - temperature sintering, the sodium source is in excess of 2 - 5% in terms of sodium element.

[0012] Further, the TM source in step (1) is one of TM oxides or TM salts.

[0013] Further, in step (1), the ball milling mixing speed is 800 - 1500 rpm, and the ball milling time is 30 - 60 min.

[0014] Further, in step (2), the sintering temperature is 800 - 1200 °C, the sintering time is 16 - 24 h, the heating rate is 2 - 10 °C / min, and the cooling rate is 2 - 10 °C / min.

[0015] Furthermore, the sieving mesh number in steps (2) and (4) is 100 to 300 meshes.

[0016] Furthermore, the double ball milling method in step (3) is to first run the cosine gradient rotation mode to reach the peak speed of the set initial cosine parameter, and then run the sine gradient rotation mode to start stirring; the whole process of the double ball milling mode needs to be performed more than once.

[0017] Furthermore, the rotation speed of the cosine gradient rotation mode in step (3) is 600-3000 rpm, the rotation speed of the sine gradient revolution mode is 400-2000 rpm, and the stirring time interval of each gradient in each rotation mode or revolution mode is 120s-10min.

[0018] Furthermore, the cosine rotation mode in step (3) refers to the regular characteristics of the rotation parameters of the ball mill jar being a composite cosine function, and the sinusoidal revolution mode refers to the regular characteristics of the revolution parameters of the ball mill jar being a composite sine function. Figure 1 .

[0019] Furthermore, in step (4), the sintering temperature is 400-600° C., the sintering time is 4-8 hours, the heating rate is 2-10° C. / min, and the cooling rate is 2-10° C. / min.

[0020] Compared with the prior art, the technical effects created by this application are embodied in:

[0021] (1) In the ball milling process of step (3), the present invention adopts the gradient rotation plus revolution resonance mode for the first time to make the layered oxide obtained in step (2) and ZrO2 contact and mix evenly. Under different speed parameters and rotation modes, due to the difference in speed, the ZrO2 in the ball mill will vibrate. When the vibration overlaps, resonance will occur, so that the large volume of ZrO2 material agglomerated during rotation is shaken and dispersed, avoiding the excessive agglomeration volume of ZrO2 material and effectively controlling the size and volume of the agglomerate. Compared with the traditional mode of ultrasonic dispersion, the present invention does not deliberately eliminate agglomeration, but induces ZrO2 material to orderly generate smaller and more agglomerates, because in the ultrasonic dispersion mode, the agglomeration that is deliberately eliminated will still immediately form agglomerates under the action of electrostatic force after losing ultrasonic vibration, resulting in uneven local load. Secondly, ZrO2 coating can effectively reduce the surface residual alkali content of the material, and hinder the reaction between the electrolyte and the material during the charge and discharge process, thereby improving the cyclic stability of the material; the ZrO2 coating layer will further introduce Zr into the layered oxide phase. 4+ , Zr with 4d orbitals 4+ The average energy of the 2P orbital electrons of O in the layered oxide will be closer to the Fermi level, making n% ZrO2@Nax The O atoms in TMO2 are more active, which makes n% ZrO2@Na x The oxygen ions of the TMO2 material undergo redox reactions within a voltage range of 2 to 4 V, thereby effectively controlling the dissolution of oxygen ions in the material.

[0022] (2) The present invention can effectively synthesize a layered oxide with a uniform ZrO2 coating layer, which can effectively hinder the generation of side reactions between the electrolyte and the layered oxide, thereby improving the interface stability of the material. 4+ The synergistic effect of doping can enhance the redox reaction activity of oxygen ions in layered oxides and control their active voltage interval within the voltage range of 2 to 4V. This method can effectively increase the discharge gram-specific capacity of layered oxide positive electrode materials, inhibit the dissolution of oxygen ions, and improve the stability of the materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the sine revolution mode and the cosine revolution mode in the ball mill stirring of the present invention.

[0024] Figure 2 For Example 1 and Example 2 and the original Na 2 / 3 Fe 1 / 2 Mn 1 / 2 XRD pattern of O2 sample.

[0025] Figure 3 This is the TEM test result of Example 1.

[0026] Figure 4 For Example 1 and Example 2 and the original Na 2 / 3 Fe 1 / 2 Mn 1 / 2 The first-week discharge image, first-week dq / dv image and rate discharge image of the O2 sample. DETAILED DESCRIPTION

[0027] The technical solution of the present application is further limited below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.

[0028] Example 1

[0029] (1) Na2CO3, Fe2O3 and MnO2 were mixed according to Na 2 / 3 Fe 1 / 2 Mn 1 / 2 The molar ratio of each element in the chemical formula of O2 is weighed and placed in a ball mill, wherein the sodium source is 3% excessive in terms of sodium element to compensate for the loss of the sodium source during high-temperature sintering, and the mixed powder is obtained by ball milling at a speed of 800 rpm for 30 minutes;

[0030] (2) The mixed powder in step (1) is transferred to a porcelain boat, the porcelain boat is placed in a tube furnace, the temperature is increased to 960° C. at a heating rate of 2° C. / min in an air atmosphere, the temperature is kept at this temperature for 16 h, and then the temperature is decreased to room temperature at a cooling rate of 2° C. / min, the sintered product is taken out, the sintered product is ground into powder, and the powder is passed through a 200-mesh sieve to obtain a sodium ion battery layered oxide Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2;

[0031] (3) placing the layered oxide obtained in step (2) in a ball mill, weighing 1 wt% ZrO2 of the layered oxide mass fraction and placing it in the ball mill, and then placing the ball mill in a planetary ball mill, and performing ball milling in a double ball milling mode; in the double ball milling mode, first running the cosine rotation mode to reach the peak speed of the set initial cosine parameter, and then running the sine rotation mode to start stirring, the specific operation conditions are shown in Table 1; the whole process of the double ball milling mode needs to be carried out more than once, and finally a mixed powder that is ball milled and mixed evenly is obtained;

[0032] Table 1

[0033]

[0034] (4) The mixed powder in step (3) was transferred to a porcelain boat, and the porcelain boat was placed in a tube furnace. The temperature was raised to 500° C. at 5° C. / min in an air atmosphere, and the temperature was kept at that temperature for 6 h. The temperature was then lowered to room temperature at 5° C. / min, and the sintered product was taken out. The sintered product was ground into powder and sieved to obtain ZrO2-coated sodium ion battery layered oxide 1% ZrO2@Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2.

[0035] Example 2

[0036] (1) Na2CO3, Fe2O3 and MnO2 were mixed according to Na 2 / 3 Fe 1 / 2 Mn 1 / 2 The molar ratio of each element in the chemical formula of O2 is weighed and placed in a ball mill, wherein the sodium source is 3% excessive in terms of sodium element to compensate for the loss of the sodium source during high-temperature sintering, and the mixed powder is obtained by ball milling at a speed of 800 rpm for 30 minutes;

[0037] (2) The mixed powder in step (1) is transferred to a porcelain boat, the porcelain boat is placed in a tube furnace, the temperature is increased to 960° C. at a heating rate of 2° C. / min in an air atmosphere, the temperature is kept at this temperature for 16 h, and then the temperature is decreased to room temperature at a cooling rate of 2° C. / min, the sintered product is taken out, the sintered product is ground into powder, and the powder is passed through a 200-mesh sieve to obtain a sodium ion battery layered oxide Na 2 / 3 Fe1 / 2 Mn 1 / 2 O2;

[0038] (3) The layered oxide obtained in step (2) is placed in a ball mill, and ZrO2 with a mass fraction of 2 wt% of the layered oxide is weighed and placed in the ball mill, and then the ball mill is placed in a planetary ball mill, and ball milling is performed in a double ball milling mode; in the double ball milling mode, the cosine rotation mode is first operated to reach the peak speed of the set initial cosine parameter, and then the sine rotation mode is operated to start stirring, and the specific operation conditions are shown in Table 2; the whole process of the double ball milling mode needs to be performed more than once, and finally a mixed powder that is ball milled and mixed evenly is obtained;

[0039] Table 2

[0040]

[0041]

[0042] (4) The mixed powder in step (3) was transferred to a porcelain boat, and the porcelain boat was placed in a tube furnace. The temperature was raised to 500° C. at 5° C. / min in an air atmosphere, and the temperature was kept at that temperature for 6 h. The temperature was then lowered to room temperature at 5° C. / min, and the sintered product was taken out. The sintered product was ground into powder and sieved to obtain ZrO2-coated sodium ion battery layered oxide 2% ZrO2@Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2.

[0043] Example 3

[0044] (1) Na2CO3, Fe2O3, MnO2 and NiO were mixed according to Na 2 / 3 Fe 1 / 3 Mn 1 / 3 Ni 1 / 3 The molar ratio of each element in the chemical formula of O2 is weighed and placed in a ball mill, wherein the sodium source is 3% excessive in terms of sodium element to compensate for the loss of the sodium source during high-temperature sintering, and the mixed powder is obtained by ball milling at a speed of 600 rpm for 60 minutes;

[0045] (2) The mixed powder in step (1) is transferred to a porcelain boat, the porcelain boat is placed in a tube furnace, the temperature is increased to 960° C. at a heating rate of 2° C. / min in an air atmosphere, the temperature is kept at this temperature for 16 h, and then the temperature is decreased to room temperature at a cooling rate of 2° C. / min, the sintered product is taken out, the sintered product is ground into powder, and the powder is passed through a 200-mesh sieve to obtain a sodium ion battery layered oxide Na 2 / 3 Fe 1 / 3 Mn 1 / 3 Ni 1 / 3O2;

[0046] (3) The layered oxide obtained in step (2) is placed in a ball mill, and ZrO2 with a mass fraction of 2 wt% of the layered oxide is weighed and placed in the ball mill, and then the ball mill is placed in a planetary ball mill, and ball milling is performed in a double ball milling mode; in the double ball milling mode, the cosine rotation mode is first operated to reach the peak speed of the set initial cosine parameter, and then the sine rotation mode is operated to start stirring, and the specific operation conditions are shown in Table 3; the whole process of the double ball milling mode needs to be performed more than once, and finally a mixed powder that is evenly mixed by ball milling is obtained;

[0047] Table 3

[0048]

[0049] (4) The mixed powder in step (3) was transferred to a porcelain boat, and the porcelain boat was placed in a tube furnace. The temperature was raised to 500° C. at 5° C. / min in an air atmosphere, and the temperature was kept at that temperature for 6 h. The temperature was then lowered to room temperature at 5° C. / min, and the sintered product was taken out. The sintered product was ground into powder and sieved to obtain ZrO2-coated sodium ion battery layered oxide 2% ZrO2@Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2.

[0050] result:

[0051] Depend on Figure 2 It can be seen that both Example 1 and Example 2 contain Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2 diffraction peaks, there are also ZrO2 diffraction peaks, indicating that the coating is relatively successful, and Zr 4+ Doping causes the (002) crystal plane of the crystal to shift.

[0052] Depend on Figure 3 It can be seen that ZrO2 is very uniformly coated on the surface of the layered oxide, and three lattice orientations appear in the high-resolution image. After Fourier transform processing, Figure 3 c is Na 2 / 3 Fe 1 / 2 Mn 1 / 2 The lattice of O2, Figure 3 b is Zr 4+ Doped Na 2 / 3 Fe 1 / 2 Mn 1 / 2 The lattice of O2, Figure 3 e is the lattice of ZrO2, which indicates that this method can realize the 4+ Synergistic modification of layered oxides by doping.

[0053] Depend on Figure 4It can be seen that the discharge gram-specific capacity and median voltage of Example 1 and Example 2 are greatly improved compared with the original sample, and a reversible oxygen ion redox platform appears near 3.4V, which indicates that the synergistic modification of ZrO2 and Zr4+ doping on layered oxides can reduce the threshold voltage of oxygen ion redox reaction from 4.2V to 3.4V, inhibit the irreversibility of layered oxides at high voltage and oxygen ion dissolution, thereby improving the electrochemical properties of the material.

[0054] Finally, it should be pointed out that the above embodiments are only representative examples of the present application. Obviously, the technical solution of the present application is not limited to the above embodiments, and there may be many variations. All variations that can be directly derived or associated with the contents disclosed in the present application by a person of ordinary skill in the art should be considered as the protection scope of the present application.

Claims

1. A method for activating the redox of oxygen ions in layered oxides by coating with ZrO2, characterized in that: The chemical formula of the layered oxide is Na x TMO2, where 0.44 < x < 0.8, and TM is selected from one or more of Fe, Mn, Ni, Al, Cu, and Zn. The method specifically includes the following steps: (1) weighing a sodium source and a transition metal source TM according to the molar ratio of each element in the chemical formula and placing them in a ball mill, and mixing them uniformly by ball milling to obtain a mixed powder; (2) transferring the mixed powder in step (1) into a porcelain boat, placing the porcelain boat in a tube furnace, sintering at high temperature in an air atmosphere, cooling to room temperature, taking out the sintered product, grinding the sintered product into powder, sieving, and obtaining a sodium ion battery layered oxide Na x TMO2; (3) placing the layered oxide obtained in step (2) in a ball mill, weighing 1 to 3 wt% of ZrO2 in the layered oxide, placing the ball mill in a planetary ball mill, and performing ball milling in a double ball milling mode; finally obtaining a uniformly mixed powder; (4) Transfer the mixed powder in step (3) to a porcelain boat, place the porcelain boat in a tube furnace, sinter at high temperature in an air atmosphere, then cool to room temperature and take out the sintered product. Grind the sintered product into powder and sieve it to obtain the layered oxide of sodium-ion battery coated with ZrO2, n% ZrO2@Na x TMO2, where 1 < n < 3, 0.44 < x < 0.8, and TM is selected from one or more of Fe, Mn, Ni, Al, Cu, and Zn.

2. The method for activating oxygen ion redox of layered oxides by coating with ZrO2 according to claim 1, characterized in that: The sodium source in step (1) is one of NaOH, Na2CO3, NaHCO3, NaCl and CH3COONa. To compensate for the loss of the sodium source during high-temperature sintering, the sodium source is in excess of 2-5% in terms of sodium element.

3. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: In the step (1), the TM source is one of a TM oxide or a TM salt.

4. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: In the step (1), the ball milling mixing speed is 800 to 1500 rpm, and the ball milling time is 30 to 60 min.

5. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: In the step (2), the sintering temperature is 800-1200° C., the sintering time is 16-24 hours, the heating rate is 2-10° C. / min, and the cooling rate is 2-10° C. / min.

6. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: The sieving mesh number in the steps (2) and (4) is 100 to 300 meshes.

7. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: The double ball milling method in step (3) is to first run the cosine gradient rotation mode to reach the peak speed of the set initial cosine parameter, and then run the sine gradient rotation mode to start stirring; the whole process of the double ball milling mode needs to be performed more than once.

8. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 7, characterized in that: The rotation speed of the cosine gradient rotation mode in step (3) is 600-3000 rpm, and the rotation speed of the sine gradient revolution mode is 400-2000 rpm. The stirring time interval of each gradient in each rotation mode or revolution mode is 120s-10min.

9. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: The cosine rotation mode in step (3) refers to the regular characteristics of the rotation parameters of the ball mill jar being a composite cosine function, and the sinusoidal revolution mode refers to the regular characteristics of the revolution parameters of the ball mill jar being a composite sine function.

10. The method of using ZrO2 coating to activate layered oxide oxygen ion redox according to claim 1, characterized in that: The sintering temperature in step (4) is 400-600° C., the sintering time is 4-8 hours, the heating rate is 2-10° C. / min, and the cooling rate is 2-10° C. / min.

Citation Information

Patent Citations

  • Preparation method and application of ultrathin carbon-coated diaphragm

    CN113193298A

  • Thermal battery intermediate layer and preparation method thereof

    CN115621479A

  • Surface-coated layered oxide and preparation method thereof, positive plate, sodium ion battery and electric equipment

    CN116143199A

  • Preparation method and application of ZrO2 surface-coated and Zr &lt; 4 + &gt;-doped layered oxide

    CN117154047A

  • Air-stable layered chromium-based positive electrode material, preparation method therefor, and sodium-ion battery

    WO2023082777A1

Cited By

  • Long-circulation high-capacity sodion layered oxide positive electrode material with low sodium-nickel mixed arrangement and preparation method and application of long-circulation high-capacity sodion layered oxide positive electrode material

    CN121394380A